Patterns of physical activity and sedentary behavior associated with overweight in brazilian adolescents - Alexandre Romero; Camila Borges; Betzabeth Villar (Revista Brasileira de Atividade Física e Saúde)
The scope of this study was to identify patterns of physical activity and sedentary behavior (PPASB) in adolescents enrolled in public schools and assess possible relationships between these patterns and overweight. This is a Cross-sectional study conducted in 2009, with the representative sample of adolescents enrolled in the fifth grade in public schools of Piracicaba, São Paulo (Brazil) consisted of 454 adolescents between 10 and 14 years of age. Physical activity, sedentary behavior and food intake information was collected through questionnaires. Anthropometric data were also collected (body mass and height). PPASB were identified through Principal Component Analysis. To characterize the association between PPASB and overweight, multiple binary logistic regression models were used. Out of 454 adolescents, 53.5% were female and 36.6% were overweight. Six PPASB were identified:  1) composed by volleyball and dance; 2) composed by soccer, video-game and computer; 3) composed by television and computer; 4) composed by dodge-ball and cycling; 5) composed by walking activity and 6) composed by gymnastics. The PPASB characterized by sedentary activities (television and computer) was associated with overweight (OR: 1.22, 95% CI: 1.02 - 1.46) after adjusted by sexual maturity, energy density and gender. In conclusions, taking a PPASB characterized mainly by spent time in front of the television and computer increases the chance of developing overweight.